Telephone-based weight loss support for patients with knee osteoarthritis: a pragmatic randomised controlled trial. Issue 4 (April 2018) - O'Brien, K.M.; Wiggers, J.; Williams, A.; Campbell, E.; Hodder, R.K.; Wolfenden, L.; Yoong, S.L.; Robson, E.K.; Haskins, R.; Kamper, S.J.; Rissel, C.; Williams, C.M.
Summary: Objective: To determine the effectiveness of telephone-based weight loss support in reducing the intensity of knee pain in patients with knee osteoarthritis, who are overweight or obese, compared to usual care. Design: We conducted a parallel randomised controlled trial (RCT), embedded within a cohort multiple RCT of patients on a waiting list for outpatient orthopaedic consultation at a tertiary referral hospital in NSW, Australia. Patients with knee osteoarthritis, classified as overweight or obese [body mass index (BMI) between ≥27 kg/m 2 and <40 kg/m 2 ] were randomly allocated to receive referral to an existing non-disease specific government funded 6-month telephone-based weight management and healthy lifestyle service or usual care. The primary outcome was knee pain intensity measured using an 11-point numerical rating scale (NRS) over 6-month follow-up. A number of secondary outcomes, including self-reported weight were measured. Data analysis was by intention-to-treat according to a pre-published analysis plan. Results: Between May 19 and June 30 2015, 120 patients were randomly assigned to the intervention (59 analysed, one post-randomisation exclusion) or usual care (60 analysed). We found no statistically significant between group differences in pain intensity [area under the curve (AUC), mean difference 5.4, 95%CI: −13.7 to 24.5, P = 0.58] or weight change at 6 months (self-reported; mean difference −0.4, 95%CI: −2.6 to 1.8, P = 0.74). Conclusions: Among patients with knee osteoarthritis who are overweight, telephone-based weight loss support, provided using an existing 6-month weight management and healthy lifestyle service did not reduce knee pain intensity or weight, compared with usual care. Trial registration number: ACTRN12615000490572